Anxiety as a mediator between symptom distress and quality of life in peritoneal dialysis patients: insights from mediation analysis and nonlinear models - Sixia Chen; Yun Wang; Sheng Feng; Mingli Shen; Fan Zhang; Kai Song; Wenwen Li; Yun- Wang (Renal Failure)
Objectives This study investigates anxiety’s role as a mediator between symptom burden and quality of life in patients undergoing peritoneal dialysis, emphasizing the potential for targeted interventions to enhance patient outcomes.Methods In a cross-sectional design, 320 peritoneal dialysis patients were recruited, with 305 providing valid responses (response rate: 95.31%). Symptom burden (occurrence and distress), anxiety levels, and quality of life were measured using validated tools. Multiple linear regression and restricted cubic spline models assessed associations, using β with a 95% confidence interval (95% CI), while mediation analysis with 1000 bootstrap samples quantified anxiety’s mediating effects.Results Participants reported an average of 8.2 ± 2.3 concurrent symptoms, with ‘worry,’, ‘tiredness’, and ‘dry skin’ being the most severe. Both symptom number (β = −0.90; 95%CI: −1.26 to −0.55) and distress (β = −1.20; 95%CI: −1.41 to −0.98) negatively correlated with quality of life. Anxiety mediated these relationships significantly, explaining 38.9% (95%CI: 18%–62%) and 33.3% (95%CI: 19%–49%) of the total effects for symptom number and distress, respectively. Restricted cubic spline models revealed an ‘L-shaped’ relationship between symptom burden and quality of life.Conclusions Anxiety significantly mediates the relationship between symptom burden and quality of life in peritoneal dialysis patients. These findings underline the importance of integrating psychological interventions and routine symptom screening into patient care to enhance quality of life. Future research should explore longitudinal designs and standardized intervention strategies.